2011
DOI: 10.1007/s00330-011-2101-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing benign from malignant parotid gland tumours: low-dose multi-phasic CT protocol with 5-minute delay

Abstract: ObjectivesTo explore the percentage enhancement wash-out ratio (PEW) and relative PEW (RPEW) of low-dose multi-phasic computed tomography (CT) in distinguishing benign from malignant parotid gland tumours.MethodsThis study was approved by the ethics committee, and informed patient consent was obtained. 51 patients with parotid tumours proven by histopathology received CT, including 18 with pleomorphic adenomas, 14 with Warthin’s tumours and 19 with malignant tumours. Size and attenuation of parotid tumours wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
1
24
0
2
Order By: Relevance
“…Although the majority of parotid lesions are benign, surgery represents the treatment of choice (3). However, due to the nearness of the facial nerve, it is very important to know the anatomical relationships in order to perform a meticulous surgical technique (6,9). Furthermore, it is very important to preoperatively know the aggressiveness of the tumour through a correct imaging assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of parotid lesions are benign, surgery represents the treatment of choice (3). However, due to the nearness of the facial nerve, it is very important to know the anatomical relationships in order to perform a meticulous surgical technique (6,9). Furthermore, it is very important to preoperatively know the aggressiveness of the tumour through a correct imaging assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Although MRI has demonstrated a better soft tissue differentiation in parotid lesion evaluation (7), contrast-enhanced CT provides useful information in tumour characterization as well as their relationships to nearby structures (8). Great importance has been given to CT imaging in differentiating salivary gland tumours basing on lesion enhancing pattern but very little has been published about this issue if compared to studies concerning the MRI findings (7)(8)(9)(10)(11). Furthermore, the improvement of multiphasic CT scanner has led to optimized protocols with increased lesion conspicuity and better definition between tumour and surrounding normal tissues.…”
Section: Original Articlementioning
confidence: 99%
“…2,5 A study found that the percentage washout ratios in contrast materialenhanced CT may reflect various characters of parotid gland neoplasms and assist in differentiating benign from malignant tumours. 6 However, conventional CT enhanced scanning can only provide two or three phases enhanced pattern of the lesions, and it does not provide absolute quantification of perfusion changes in parotid gland lesions. CT perfusion (CTP) imaging involves the non-invasive measurement of blood volume of the lesions at the capillary level.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, they always present as painless, slowgrowing lumps and there are no specific manifestations in laboratory and traditional maging examinations. Even though, previous studies showed that multiple lesions, smoking and olderly male are helpful to suggest WTs, there are still many overlapping features are confusing and difficult to diagnosis and claify before operation [3][4][5] . Fine needle aspiration (FNA) is considered to be gold standard for parotid tumors diagnosis, but has some limitations, even under optimum conditions and may be associated with poor levels of diagnostic accuracy [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Dual or three phases enhanced examination has been currently the primarily method for the assessment of the parotid tumors [3,4,9] . Based on previous literatures [9][10][11] , it is known that washout time (or washout ratio) of contrast agents in the tumors could provide many valuable physiopathology information and help to differential diagnosis among of pariod gland lesions.…”
Section: Introductionmentioning
confidence: 99%